Grammar - Thornbury, Scott, 1950- (Oxford, New York Oxford University Press, 2009)
Helps teachers extend their range of techniques for teaching grammar to secondary and adult students. Scott Thornbury's up-to-date treatment of the many different approaches to grammar uses new ideas and adaptable activities to help teachers become more versatile and resourceful in the classroom.
Include Glossary and Index
Keywords: English language--Grammar--Study and teaching -- English language--Grammar--Study and teaching (Secondary)